Conservative Treatment of Dentigerous Cyst by Marsupialization in a Young Female Patient: A Case Report and Review of the Literature - Layal Ghandour; Hisham F. Bahmad; Samar Bou-Assi (Hindawi Limited, 2018)
Dentigerous cysts (DCs) are the most prevalent developmental odontogenic cysts that occur in middle-aged individuals. They frequently originate from the epithelial remnants of tooth-forming organs. Hereby, we present a case of a 13-year-old young female patient presenting with DC that was treated successfully by marsupialization. The patient's chief complaint was the crowding of the anterior teeth. Clinical examination showed that the patient had all her permanent teeth present with a retained mandibular left second primary molar that was previously treated by pulpectomy. The radiographic examination revealed a unilocular radiolucent lesion with well-defined margins associated with a mesially-tipped unerupted mandibular left second premolar. The differential diagnosis confirmed that the lesion was a DC. The treatment consisted of surgical removal of the DC to allow proper eruption of the permanent tooth and to prevent the lesion from becoming an aggressive one causing gross expansion of bone with subsequent facial asymmetry, pain, displacement of teeth, and root resorption. A removable acrylic obturator was delivered to the patient keeping the path clear and guiding the eruption of the premolar until fully erupted.